PXR: Structure-specific activation by hepatotoxic pyrrolizidine alkaloids. (25th May 2018) - Luckert, Claudia; Braeuning, Albert; Lampen, Alfonso; Hessel-Pras, Stefanie
Abstract: Pyrrolizidine alkaloids (PAs) comprise a large group of more than 660 secondary metabolites found in more than 6000 plant species worldwide. Acute PA intoxication induces severe liver damage. Chronic exposure to sub-lethal doses may cause cumulative damage or cancer. Nuclear receptor activation often constitutes a molecular event for xenobiotic-induced toxicity. However, so far nothing is known about potential interactions of PAs with nuclear receptors as a toxicological mode of action. Thus, in the present study PA-dependent activation of a comprehensive panel of nuclear receptors (PPARs, LXRα, RARα, RXRα, FXR, CAR, PXR, ERα/β) was investigated using GAL4/UAS-based transactivation reporter gene assays. To cover the most frequently occurring PA structure types (retronecine, heliotridine and otonecine type; as well as monoester, open-chain diester and cyclic diester) different PAs were analyzed for interaction with nuclear receptors. Most of the nuclear receptors investigated were not affected by the tested PAs. However, significant activation was found for PXR, which was exclusively activated by the open-chain diesters, echimidine and lasiocarpine. Induction of the model PXR target gene CYP3A4 by PAs was verified at the mRNA, protein and enzyme activity level. In conclusion, PXR activation and PXR-mediated induction of CYP3A4 expression by PAs seem to be structure-dependent. Data suggest that only open-chain diesters act as PXR agonists. This might imply that a PXR-mediated mode of action may contribute to the hepatotoxicity of PAs that is dependent on PA structure. Highlights: PAs can activate the human nuclear receptor PXR. PXR activation by Em leads to higher CYP3A4 mRNA level and enzyme activity. Activation of PXR appears to be dependent on PA structure. PXR is only activated by the open-chain PA diesters Em and Lc. Combination effects of Em and Lc on PXR activation follow the assumption of dose addition.